PENGUATAN LITERASI PESANTREN MELALUI JURNALIS SANTRI (Studi pada Komunitas Literasi Tebuireng) - Alfi Nabila, Alfi Nabila; Sayidah Afyatul Masruroh (Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
In an era of very rapid technological development, the Pesantren Tebuireng is consciously opening itself up and utilizing digital technology to progress and keep up with the times. One of them is by building and developing a literacy culture in Islamic boarding schools through literacy communities that form students who are proficient or competent in literacy. Part of this is to build Islamic boarding school information media to spread da'wah. This research intends to find out how the Tebuireng Islamic Boarding School implements a culture of literacy for its students, how the program run by the Islamic boarding school is to form students as Islamic boarding school journalists and how the students experience the program. This research was carried out at the Tebuireng Islamic Boarding School by interviewing several students who were actively involved in the literacy community, as well as reviewing documents carried out on the Pesantren Pesantren's website (tebuireng.online). The results of this research show that; 1) Tebuireng Islamic Boarding School implements a culture of literacy through a literacy community, 2) Tebuireng Islamic Boarding School involves students as subjects of dawah from the Islamic boarding school, 3) Tebuireng Islamic Boarding School creates literacy support programs through media managed by students who are active in the media sector / called student journalists.